A influência das características pessoais dos coordenadores no desempenho dos programas de pós-graduação stricto sensu, considerando o papel moderador do managerial discretion: pesquisa baseada na teoria do alto escalão - Belfort, Ana Claudia (2019)
Considering the upper echelon perspective, which argues that the personal characteristics of the main executives of the companies influence the performance of such entities, and the lack of studies on this subject in the context of the stricto sensu programs, this research seeks to analyze the influence of the personal characteristics of the companies coordinators in the performance of the graduate programs stricto sensu, considering the moderating role of managerial discretion. To achieve this, three studies (one theoretical and two empirical studies) were carried out. The first work consists of a bibliometric study, with analysis of citations, co-citations and network of co-citations regarding managerial discretion, one of the theoretical bases for the subsequent studies. The second work consists of a quantitative research based on data gathered from CAPES, related to the results of the Triennial Evaluation 2010-2013 and the Quadrennial Evaluation 2014-2017, which allowed to identify the evolution of existing programs and groups of programs, classified according to modalities and program level, legal status of the institution and region where it is located. Descriptive analysis and clustering were the analysis procedures adopted in this study, the result of which contributed to the following work. The third study consisted of identifying and analyzing the effects of the personal characteristics of the coordinators of the stricto sensu on the performance of the program, considering the moderating role of managerial discretion, through the application of a semi-structured questionnaire to the coordinators, elaborated based on the hypotheses based on a confirmatory factorial analysis, logistic regression analysis and t-test. Theoretical contributions include the extension of the study from a upper echelon perspective to other contexts, evolving in the analysis about the influence of the characteristics of the coordinators of stricto sensu postgraduate courses (here considered high-ranking) on the performance of the programs with basis of the CAPES evaluation system; and considering the moderation of the managerial discretion. The contributions to the practice focus on the fact that the present study can serve as a guideline for the HEIs in order to identify the coordinators for their stricto sensu programs, making it possible to identify the best set of personal characteristics of the coordinators that will positively influence the performance from the program.